Does engagement with frontline health workers improve maternal and child healthcare utilisation and outcomes in India? - Anu Rammohan; Srinivas Goli; Shashi Kala Saroj; C. P. Abdul Jaleel (Human Resources for Health, 2021)
Abstract Background Poor Maternal and Child Health (MCH) outcomes pose challenges to India’s ability to attain Goal-3 of the Sustainable Development Goals (SDGs). The government of India strengthened the existing network of frontline health workers (FHWs), under its National Rural Health Mission in 2005 and subsequent National Urban Health Mission in 2013 as a strategy to mitigate the shortage of skilled health workers and to provide affordable healthcare services. However, there is a lack of robust national-level empirical analysis on the role of maternal engagement with FHWs in influencing the level of maternal and child health care utilisation and child health outcomes in India. Methods Using data from the nationally representative Indian National Family Health Survey (NFHS) 2015–2016, this paper aims to investigate the intensity of engagement of FHWs with married women of child-bearing age (15–49 years), its influence on utilisation of maternal and child healthcare services, and child health outcomes. Our empirical analyses use multivariate regression analyses, focusing on five maternal and child health indicators: antenatal care visits (ANC) (4 or > 4 times), institutional delivery, full-immunisation of children, postnatal care (PNC) (within 2 days of delivery), and child survival. Results Our analysis finds that maternal engagement with FHWs is statistically significant and a positive predictor of maternal and child health care utilisation, and child survival. Further, the level of engagement with FHWs is particularly important for women from economically poor households. Our robustness checks across sub-samples of women who delivered only in public health institutions and those from rural areas provides an additional confidence in our main results. Conclusions From a policy perspective, our findings highlight that strengthening the network of FHWs in the areas where they are in shortage which can help in further improving the utilisation of maternal and child healthcare services, and health outcomes. Also, the role of FHWs in the government health system needs to be enhanced by improving skills, working environment, and greater financial incentives.